Enhancement of congestion control of Constrained Application Protocol/Congestion Control/Advanced for Internet of Things environment. (November 2016) - Lee, Jung June; Kim, Kyung Tae; Youn, Hee Yong
With the wide spread of Internet of Things, efficient communication between the nodes is getting more important. Constrained Application Protocol was developed to accommodate the resource-constrained nodes and low-power communication links. Being an Internet protocol, Constrained Application Protocol must adhere to congestion control, primarily to keep the backbone network stable. An advanced congestion control mechanism for Constrained Application Protocol, called Congestion Control/Advanced, has also been recently developed. In this article, we propose a new round trip time–based adaptive congestion control scheme, which further improves Congestion Control/Advanced by utilizing the retransmission count in estimating the retransmission timeout value and the lower bound in round trip time variation. An experiment is conducted based on Californium Constrained Application Protocol framework and real devices, and the performance is compared with Constrained Application Protocol, Congestion Control/Advanced, and an existing scheme. It reveals that the proposed scheme significantly increases the throughput and rate of successful transactions in comparison with the other schemes. The approach of utilizing the option field of Constrained Application Protocol enables the proposed scheme to be implemented without any conflict with the existing protocol and extra overhead.